Nos bares, cafés e restaurantes de Porto Alegre: cultura material e o ideário moderno em meados do século XX. - Nunes, Daniel Minossi (2014)
During the first half of the twentieth century, the city of Porto Alegre/RS, experienced great transformations and urban reforms, such as opening and widening of streets,construction of the new port and the substantial improvement in the harbor area, and the construction of the first skyscrapers and verticalization of the urban landscape. Especially in downtown, the intensification of the modernization process was simultaneously associated with new social practices and new experiences of different social groups in Porto Alegre. In this sense, coffee shops, restaurants, bars and hotels were typically urban public spaces that favored all kinds of social relations, where were propagated and displayed the values associated with modern ideas. Therefore, this research investigates how the commercial tablewares in the state capital acted in the production and maintenance of social groups identified with an urban, elitist and modern lifestyle. The actor-network approach, applied to the present study of historical archeology, allowed tracing the unfailing action of the commercial wares in the chronics, administrative documents, filmic records and daily life of the population of Porto Alegre. By pursuing these objects in different information sources, we sought to emphasize the non-human dimension of social relations, especially considering the participation of the commercial tablewares in the construction and maintaining of the a hegemonic masculinity. Masculinity pattern notably inserted into an urban, industrial, bourgeois and capitalist order - a modern society.